2019
DOI: 10.1080/24734306.2019.1705596
|View full text |Cite
|
Sign up to set email alerts
|

Use of fomepizole as an adjunct in the treatment of acetaminophen overdose: a case series

Abstract: Acetaminophen toxicity remains a leading cause of acute liver failure in the United States and world-wide. Fomepizole is a cytochrome P450 inhibitor that may inhibit production of toxic metabolites of acetaminophen. However there are limited clinical data of its use for this purpose in the literature. Here we present a case series of six patients treated with fomepizole for acute acetaminophen toxicity who sustained no substantial liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Widespread clinical data regarding the efficacy of fomepizole in acetaminophen toxicity remains sparse. In a series of six cases treated with fomepizole due to persistently elevated acetaminophen concentration levels at levels at risk of developing hepatic injury, Rampon et al documented the successful management of six pediatric and adult patients treated with a combination of NAC therapy and fomepizole with no hepatic injury [20]. The decision to use fomepizole in these patients was because of the persistently elevated [APAP] despite intravenous NAC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread clinical data regarding the efficacy of fomepizole in acetaminophen toxicity remains sparse. In a series of six cases treated with fomepizole due to persistently elevated acetaminophen concentration levels at levels at risk of developing hepatic injury, Rampon et al documented the successful management of six pediatric and adult patients treated with a combination of NAC therapy and fomepizole with no hepatic injury [20]. The decision to use fomepizole in these patients was because of the persistently elevated [APAP] despite intravenous NAC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse side effects associated with intravenous administration include flushing, rash, nausea, vomiting, and itching, besides tachycardia, bronchospasm, and hypotension in severe cases (1,3). They occur in the first two hours after infusion in 15% of patients (3,11). Some patients presented oliguria, anuria, uremia, and a 40% reduction in GFR on the first day of overdosing on NAC, leading to acute kidney failure (12).…”
Section: Discussionmentioning
confidence: 99%
“…40 Besides, some studies reported the efficacy of fomepizole in treating acetaminophen exposure. [41][42][43][44] Hemodialysis is reported as an effective treatment in the severe acetaminophen exposure. 45,46 However, hemodialysis is generally not recommended to treat acetaminophen-poisoned patients.…”
Section: Discussionmentioning
confidence: 99%